Facilitating Advance Care Planning for Patients With Severe COPD: A Qualitative Study of Experiences and Perceptions of Community Physicians, Nurses, and Allied Health Professionals. (March 2021) - Hirakawa, Yoshihisa; Aita, Kaoruko; Nishikawa, Mitsunori; Arai, Hidenori; Miura, Hisayuki
Abstract : Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity worldwide. Patients with severe COPD often fail to receive adequate palliative care and are subject to undesired hospital transfers and cardiopulmonary resuscitation. Although promoting advance care planning (ACP) in the community can help ensure the optimal delivery of palliative care for patients with COPD, the key challenges to routinely implementing ACP are not known. The aim of this study was to identify the perception of healthcare professionals with regard to ACP for adults living with severe COPD and the challenges to facilitating ACP. A multicenter qualitative study design was used. In-depth semistructured interviews were held involving 38 healthcare professionals from 19 institutions in Japan. Text data were analyzed by content analysis. Five main themes capturing the challenges to routine implementation of ACP were identified: daily decision-making; sense of ethical decision-making; in-depth interviewing skills; collaborative information sharing among team members; and knowledge dissemination regarding ACP. The model demonstrates the complexity inherent in ACP facilitation for community-dwelling adults with severe COPD, with all the elements required for successful ACP implementation. We recommend an approach that recognizes the importance of stakeholder education, particularly educating professionals to develop the knowledge, attitudes, and skills required for ACP facilitation: in-depth interviewing, collaborative information sharing, and ethical analysis, focusing on decision-making concerning everyday life support.